End of Story : a Novel - Finn, A. J. (New York : William Morrow, an imprint of HarperCollinsPublishers, 2024)
Invited by a reclusive mystery novelist to help draft his life story, a longtime correspondent and detective fiction expert finds herself in a real whodunnit when she learns the writer's first wife and son mysteriously vanished.
Includes bibliographical references (pages 407- 408)
Keywords: Novelists -- Fiction; Recluses -- Fiction; Cold cases (Criminal investigation) -- Fiction; Missing persons -- Investigation -- Fiction; Murder -- Investigation -- Fiction; Mansions -- California -- San Francisco -- Fiction; San Francisco (Calif.) -- Fiction; Thrillers (Fiction); Psychological fiction